Analisis Perlindungan Hak Cipta Penggunaan Nama & Visual Artis Korea (SM Entertainment) Pada Novel & Serial “Dikta dan Hukum” - Khaira Alfiyya Irwandi (Lembaga Pengembangan Kinerja Dosen, 2024)
Korean fever or often referred to as the Hallyu Wave is now continuing to grow along with technological developments and ease of internet access. Dikta and Law, by Dhia'an Farah, is one of the many popular fiction stories that is fortunate to be currently being broadcast as a series on WeTV. However, behind the success of the Dikta and Hukum story, there was controversy that arose. The name Jeno, one of the characters in the story Dikta and Hukum, has become a debate on social media, especially for NCT Dream fans. The reason is, Jeno is the stage name of one of the members of NCT Dream (Lee Jeno) and is considered to be used illegally in the Dikta and Hukum series. This controversy arose because the novel writer and series production party used the name Jeno without the permission of the name owner or his agency, namely SM Entertainment. This research aims to analyze copyright protection for the use of names and visuals of Korean artists (SM Entertainment) in the novel and series